Criação de fótons no efeito Casimir dinâmico em cavidade oscilante com condições de Neumann e Dirichlet - GRANHEN, Edney Ramos (Universidade Federal do Pará, 2014)
We consider a massless scalar field in a two-dimensional space-time inside an oscillating cavity with mixed boundary conditions. In order to discuss particle creation phenomenum, we consider the situation of parametric resonance in which the oscillating frequency is twice the frequency of the first mode of the static cavity. For convenience, we suppose that one of the boundaries is at rest and imposes Neumann condition to the field, whereas the other is in non-relativistic motion and imposes a Dirichlet condition on the field. Following the procedure developed by Dodonov and Klimov (Phys. Rev. A, 56, 2664 (1996)), we compute the number of created particles, the generation rate and the energy in the cavity. We compare our results with those found in the literature for the Dirichlet-Dirichlet case.